Probing the energy reactance with adiabatically driven quantum dots - Ludovico, María Florencia (2018)
The tunneling Hamiltonian describes a particle transfer from one region to another. Although there is no particle storage in the tunneling region itself, it has an associated amount of energy. The corresponding energy flux was named reactance since, such as an electrical reactance, it manifests itself in time-dependent transport only. We show here that the existence of the energy reactance leads to the universal response of a mesoscopic thermometer, a floating contact coupled to an adiabatically driven quantum dot.